An empirical investigation of procurement trends and partnership management in FM services – A Finnish survey - Lehtonen, Tero; Salonen, Anssi (International Journal of Strategic Property Management, 2010)
The aim of this paper is to review procurement trends of facilities management (FM) services and to describe the partnership control mechanisms that contribute to the success of FM partnerships. The investigation is based on a questionnaire survey, which was carried out in Finland. It was found that a transition – similar to those in other industries – towards closer relationships and bigger purchase entities is taking place also in the FM context. In most cases, the choice of the partnering approach is related to developing wider service packages. When implementing partnering relationships, the task of top management is to provide the shared values and visions. Having established these in the organisation, top management does not seem to have any significant role in relationship management. During the ongoing partnership, the operational level runs the daily initiative, development and problem solving based on ad hoc procedures. First Published Online: 18 Oct 2010